Subsistence of English Area Program in Enhancing Teenagers’ English Skill in Majene Regency - Asdar Asdar; Dwi Adi Nugroho; Hustiana Hustiana (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
This study aspired to represent the concessions of executing English Area for teenagers on their English language skills. In this case, four skills are incorporated into the enactment process. The implementation of this study was conducted at SMA 3 Majene which is a boarding school student. This study used a quantitative descriptive method where there were 28 samples from 58 populations who participated in the data collection process. The instrument used is a test consisting of a pre-test and post-test, and an observation guide. From the results of observation, the prominent skill was speaking skill which was seen from several activities, namely providing material, morning talk, talk show, talent night, and treasure hunt consisting of five activities, namely Spelling bee, Word Guessing, Constructing Sentences, Once Upon A Time, Arrange the picture. This was in line with the test results which showed that this program could improve students' speaking skills with an average score of -0.767. The researchers concluded that this program can improve speaking, but it did not have much effect on other skills. Therefore, researchers recommended that further research can construct more active activities furthermore all skills can be covered. This research can provide benefits for pre-service teachers who can use this research as a reference for carrying out activities in the classroom. It was also useful for future researchers who wanted to develop English area programs in other places or by using different indicators.